Find optimal preventive maintenance time using linear programming - Faris Mahdi Alwan; Ghosoon Harbi Abbas (Journal of Madenat Alelem University College, 2018)
Preventive maintenance is of great importance in the maintenance of machines and prevent the sudden discontinuation of the devices. The main objective of this research is to determine the optimal time for preventive maintenance. The research depended on the linear programming method in estimating the optimal period of preventive maintenance. The study was carried out at the Neuroscience Hospital Where the study of the stops that affect the medical devices through the records of the hospital and through the collection of data on the site was selected device anesthesia device and Ventilator and monitor and sterilization device as it recorded the highest failures compared to the rest of the devices and In this research, linear mathematical model was formulated and solved in Win-QSB and the results were shown The cost of maintaining an anesthesia machine is 2,500.00 million dinars every five months. The cost of maintenance of the ventilator is 350,000 thousand dinars every seven months. The cost of maintenance of the monitor is 100,000 thousand dinars every eight months. The cost of maintaining sterilization apparatus is 500,000 Thousand dinars annually, every 12 months compared to the current reality of the hospital where the anesthesia vehicle is maintained by changing the solutions every three months and cost the hospital (5,000,000) million dinars, while Ventilator is maintained every two months by changing the filter in the device and specialist entry Air and discharged to the patient and withdraw moisture from it, where the cost of the hospital (1,050,000) million dinars, as well as the monitor device is maintained by lubrication and lubrication every 6 months and the cost of the hospital (200,000) thousand dinars and sterilization device is maintained every 40 hours by the work Reset the device and the filters in it are changed every month and this costs the hospital (60,000,000) million dinars. We conclude from this that planning using the linear programming method is better than the planning followed by the hospital in terms of maintenance of the devices, where the cost of maintenance of the devices has been reduced and this indicates the efficiency of the mathematical model.